2016
DOI: 10.1127/fal/2016/0963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-level fluctuations on the environmental characteristics and fish-environment relationships in the littoral zone of a reservoir

Abstract: Water-level fluctuations are a major function of reservoirs that influence the littoral zone of the lake, and prove to be of high importance for the whole biological communities of lakes. Working on a French hydropower reservoir, we studied the influence of water-level fluctuations on intra-annual variations of littoral habitat availability and their consequences for the structure of fish assemblages inhabiting the littoral zone. As the water level decreased significantly, habitat conditions tended to be much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
1
26
0
4
Order By: Relevance
“…These results, based on the entire lake, are in agreement with other studies (Gasith & Gafny, 1990;Gasith & Gafny, 1998), and mean that lowering WL correspond to fewer refuge areas and probably fewer food resources for perch (Zohary & Ostrovsky, 2011;Zohary & Gasith, 2014). They also confirmed the trends observed by Logez et al (2016) with a point sampling on the same lake, but brought additional information as the stable availability of littoral tree stumps with WL and the rise of the relative availability and surface of the littoral area when the WL dropped.…”
Section: Variability Of Habitat Availability With Wlsupporting
confidence: 81%
See 4 more Smart Citations
“…These results, based on the entire lake, are in agreement with other studies (Gasith & Gafny, 1990;Gasith & Gafny, 1998), and mean that lowering WL correspond to fewer refuge areas and probably fewer food resources for perch (Zohary & Ostrovsky, 2011;Zohary & Gasith, 2014). They also confirmed the trends observed by Logez et al (2016) with a point sampling on the same lake, but brought additional information as the stable availability of littoral tree stumps with WL and the rise of the relative availability and surface of the littoral area when the WL dropped.…”
Section: Variability Of Habitat Availability With Wlsupporting
confidence: 81%
“…In the same reservoir in summer and autumn, Logez et al (2016) observed that the littoral fish assemblages, composed of juveniles and adults, were dependent on the WL and tended to homogenize when the habitat complexity lowered, suggesting variations in habitat use when its availability changed, even if adults seemed to be the less affected. Considering the advantages of the littoral zone for fish fauna (Schiemer et al, 1995;Schmieder, 2004;Lewin et al, 2014) and the importance of the habitats impacted by WLF for perch (Imbrock et al, 1996;Zamora & Moreno-Amich, 2002;Pekcan-Hekim et al, 2005;Cech et al, 2009;Muska et al, 2013), we expected some changes in the habitat preferences at different WL.…”
Section: Influence Of Wl On Habitat Preferencementioning
confidence: 93%
See 3 more Smart Citations